Peningkatan Daya Saing UMKM Produk untuk Hewan Peliharaan dengan Analisis SWOT - I Gusti Ayu Sri Deviyanti; Alycia Lauren; Keryn Rahmawati Ferryanto; Waldy Renaldo Hamonangan Turnip (Journal of Industrial Innovation and Safety Engineering (JINSENG), 2026)
The public's trend of keeping pets, especially dogs and cats, is currently increasing. This has given rise to a trend of numerous pet food and snack manufacturing industries. One of these is Juju Paws. This research was conducted due to the intense market competition faced by many similar industries, such as Juju Paws. This research aims to develop strategies that can enable MSMEs to compete more effectively with similar competitors. In order to collect data, the research used observation, interviews, and documentation methods. The collected data were analyzed using the SWOT method. To ensure data accuracy, the researcher also triangulated data sources. The results of the data analysis, which used the IFAS matrix and the EFAS matrix, and the SWOT Cartesian Diagram, produced a strategy located in quadrant I or the growth quadrant in the IE matrix. This position indicates that the strengths and opportunities are more dominant than weaknesses and threats, so the business is in good condition and has the potential to grow more aggressively. The ST (Strengths-Threats) strategy indicates this strategy focuses on utilizing the strengths possessed by MSMEs (Strengths) to overcome existing threats (Threats). Some recommendations given are holding various attractive promotions, using more attractive packaging, participating in every pet-related event, products with smaller packaging sizes to be more affordable for consumers, and introducing custom hamper services according to variants and budgets.